Hubungan Iklim, Kepadatan Nyamuk Anopheles dan Kejadian Penyakit Malaria - SUWITO SUWITO; UPIK K HADI; SINGGIH H SIGIT; SUPRATMAN SUKOWATI (Jurnal Entomologi Indonesia, 2010)
Districts of South Lampung and Pesawaran are malaria endemic areas. The purpose of this study was to analyze the relationship between climate, Anopheles density and malaria incidence. Mosquito collections were caught by human landing collection all night 06:00 PM-06:00 AM. The relation of climate with Anopheles density and Anopheles density with malaria incidence were analysed by Pearson Product Moment test. The Anopheles bite all night, peaks with 02:00-04:00 AM, outdoor bitings were more frequent than indoor biting. There were relationships between relative humidity and rain fall with Anopheles density, and Anopheles density with malaria incidence one month later.